2018
DOI: 10.3201/eid2401.171297
|View full text |Cite
|
Sign up to set email alerts
|

Japanese Encephalitis Virus Transmitted Via Blood Transfusion, Hong Kong, China

Abstract: Japanese encephalitis virus (JEV) is a mosquitoborne virus endemic to China and Southeast Asia that causes severe encephalitis in <1% of infected persons. Transmission of JEV via blood transfusion has not been reported. We report transmission of JEV via blood donation products from an asymptomatic viremic donor to 2 immunocompromised recipients. One recipient on high-dose immunosuppressive drugs received JEV-positive packed red blood cells after a double lung transplant; severe encephalitis and a poor clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 37 publications
(31 reference statements)
0
27
0
1
Order By: Relevance
“…In Hong Kong, JEV was transmitted to a lung transplant recipient by an RBC unit from an asymptomatic blood donor, resulting in encephalitis and death in the recipient. JEV sequences in a sample from the donation were identical to those in the recipient . In the United States, a case of SLEV neuroinvasive disease in a kidney transplant recipient was traced to an RBC unit from an asymptomatic blood donor who was demonstrated to have SLEV immunoglobulin M in a sample collected 77 days after donation .…”
Section: Discussionmentioning
confidence: 85%
“…In Hong Kong, JEV was transmitted to a lung transplant recipient by an RBC unit from an asymptomatic blood donor, resulting in encephalitis and death in the recipient. JEV sequences in a sample from the donation were identical to those in the recipient . In the United States, a case of SLEV neuroinvasive disease in a kidney transplant recipient was traced to an RBC unit from an asymptomatic blood donor who was demonstrated to have SLEV immunoglobulin M in a sample collected 77 days after donation .…”
Section: Discussionmentioning
confidence: 85%
“…Had the WNV testing occurred during the period of potential indigenous WNV exposure in Canada (between early June and the end of November, when universal blood donor WNV screening is conducted by CBS), a positive WNV screening minipool assay would also have activated a one‐week period of individual WNV testing for collections in the region where exposure was thought to have occurred. Our findings suggest that proper assessment of the travel history of a WNV‐positive blood donor should also consider the epidemiology of other members of the JEV serocomplex which may also be detected by this donor screening assay, several of which (including JEV and Usutsu), have also been described in blood donors . In the five cases described here, a key relevant consideration is that each donor received Ixiaro JEV vaccine within 3 days prior to donation.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, JEV can be passed directly from an infected female Culex or non- Culex mosquito to her eggs, suggesting the transovarial transmission as a mechanism by which the virus overwinters in the environment [ 70 , 71 , 72 , 73 ]. In addition, in terms of non-vector-borne transmission, a recent report has indicated that JEV can be transmitted through the transfusion of contaminated blood products [ 74 ].…”
Section: Jev Is a Zoonotic Pathogen Capable Of Infecting A Wide Ramentioning
confidence: 99%